Theoretical and experimental substantiation of receiving a pharmaceutical composition in the form of a cryogel with lidocain hydrochloride and decametoxin - A. M. Solomennyi; A. O. Drozdova (The State Expert Center of the Ministry of Health of Ukraine, 2023)
Modern medicines for the treatment of wounds are developed on the basis of knowledge about their phase healing. The main principle of wound treatment is the creation and maintenance of a moist environment, stable temperature, absorption of excess exudate, minimization of the risk of sensitization, increased intervals between dressings, easy removal of coatings from the surface of the wound. The implementation of this principle is the basis of our research on the creation of a cryogel - a supermacroporous hydrogel that is formed at subzero temperatures by polymerization of monomers or cryogel formation of oligomers without the use of toxic organic solvents and with controlled textural and structural characteristics. A comprehensive study of cryogels has like theoretical as practical interest, because they can serve as a perspectiving new material in pharmacy for obtaining new medicines. The purpose of our research was to substantiate the composition of the cryogel with lidocaine hydrochloride and decamethoxine based on the conducted pharmacotechnological, physicochemical and biopharmaceutical research methods. Model samples (№№ 1-10) with different contents of lidocaine hydrochloride, decamethoxine, and auxiliary substances were selected as research objects. Pharmacotechnological, physicochemical and biopharmaceutical research methods were used. The technological and biopharmaceutical factors of development pharmaceutical composition in the form of a cryogel with lidocaine hydrochloride and decamethoxine were studied. Based on the results of the research, we found that samples (№№ 1-10) are homogeneous without signs of delamination, no changes are observed (aggregation of particles, sediment, odor). Samples №№ 3, 9 and 10 differ in the presence/absence of API. It was shown that APIs do not affect the absorption capacity of the studied samples. Comparative studies confirm our assumption that the presence of PG in the cryogel increases the absorption of liquid by the samples. The prolongation of the action in the composition depends on the presence of PG in the sample of composition. The prolonged effect of pharmaceutical composition was established. For further research, sample № 10 (lidocaine hydrochloride - 0.4; decamethoxine - 0.03; PVA 15% - 20.0; PG - 10.0) was chosen.